Establishing Philosophy for the Development of School Curriculum - Dhungana, Jiwan (Education and Development, 2022)
This paper is an attempt to explore the guidelines for establishing philosophy for school curriculum development. It is a theoretical article that consulted several philosophies, theories, books, and research articles to understand multiple realities and issues of philosophy concerning curriculum development. The data collection and analysis were organized with global themes that emerged through the review of different literature. The paper has analyzed that the curriculum development process required a particular process rather than employing an established philosophy. The curriculum depends upon what society has understood about education and should be designed upon building such society which the society aspires to transform into. The legal and political system, educational philosophies, global and local philosophical perspectives of curriculum development, curriculum conceptions, and contemporary educational issues are the major influencing factors to ponder upon for developing a philosophy of school curriculum.